1923
DOI: 10.1002/zaac.19241320123
|View full text |Cite
|
Sign up to set email alerts
|

Über die Alterung des Chromhydroxydes, sowie über Alkalichromite und ihre Lösungen

Abstract: 1. Es wurden Löslichkeitskurven von ganz reinem Chromhydroxyd (Zusammensetzung ungefähr: Cr2O3·9 H2O) in Alkalilaugen bei Zimmertemperatur aufgenommen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1933
1933
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although precipitation of Cr(OH) 3 at these moderate pH values takes place rapidly (Fricke and Windhausen, 1923;Rai et al, 1987), no visible coagulations were observed for the first 120 h. We speculate that small isotope fractionation during precipitation of Cr(OH) 3 , adsorption effects and contamination of the separated Cr(VI) with particulate Cr(III), which did not wash out from the anion exchange resin together with soluble Cr(III) during species separation, are responsible for the small change in isotopic compositions of Cr(III) and Cr(VI) complexes over extended experimental run times.…”
Section: Isotopic Exchange Experimentsmentioning
confidence: 99%
“…Although precipitation of Cr(OH) 3 at these moderate pH values takes place rapidly (Fricke and Windhausen, 1923;Rai et al, 1987), no visible coagulations were observed for the first 120 h. We speculate that small isotope fractionation during precipitation of Cr(OH) 3 , adsorption effects and contamination of the separated Cr(VI) with particulate Cr(III), which did not wash out from the anion exchange resin together with soluble Cr(III) during species separation, are responsible for the small change in isotopic compositions of Cr(III) and Cr(VI) complexes over extended experimental run times.…”
Section: Isotopic Exchange Experimentsmentioning
confidence: 99%